Preliminary study of production electrolytic silicon from silica amorphous in alkaline media - Muhammad Miftahur Rahman; Franky Michael Hamonangan Siagian; Yogi Tri Putra Nasution; Widi Astuti; Ulung Sutopo; Himawan Tri Bayu Murti Petrus (CHEMICA: Jurnal Teknik Kimia, 2023)
This study used direct electrowinning to examine the viability of producing silicon from amorphous silica in alkaline conditions. The Indonesian Dieng Geothermal Power Plant provided a sample of geothermal sludge with a high silica (SiO2) content. The samples were analyzed using various analytical techniques (XRF and XRD) before to electrolysis to ascertain their chemical composition and mineralogy. At low temperatures (30°C), the direct electrowinning method using amorphous silica suspended in sodium hydroxide (NaOH) was introduced. Current density adjustments were made to determine the direct electrowinning method's ideal operation. XRD and XRF analyses were performed on cathode deposits and residues in electrochemical cells to ascertain the chemical composition and current recovery. At a current density of 1250 A/m2, the low-temperature electrolysis current efficiency on natrium silicate solution can approach 34% recovery. Geothermal sludge was used to investigate the process, and the process's mediocre performance was caused by the problematic adsorption of amorphous silica particles on the cathode.